FTIR-GUIDED ETHYL ACETATE EXTRACTION OF ANDROGRAPHIS PANICULATA: SPECTROSCOPIC CHARACTERIZATION AND INFERRED THERAPEUTIC POTENTIAL - Ladipo, Margaret Kudirat; Ojokuku, Sikiru Abiola; Odusami, Jocelyn Adelanke; Atanda, Saburi Abimbola (FUDMA JOURNAL OF SCIENCES, 2025)
The increasing demand for standardized herbal medicines necessitates the development of rapid analytical methods for phytochemical characterization and quality assessment. Andrographis paniculata (King of Bitters), despite its established therapeutic properties in traditional medicine, lacks a comprehensive spectroscopic analysis correlating molecular fingerprints with bioactive potential. This study employed FTIR spectroscopy to characterize ethyl acetate extracts of A. paniculata aerial parts and correlate spectral features with potential therapeutic applications. Ethyl acetate extraction yielded 3.2 ± 0.3% w/w dry weight with distinctive FTIR fingerprints revealing 15 characteristic absorption bands. Key spectral features included dual free O-H stretching at 3555 and 3474 cm⁻¹ (phenolic aglycones), ester carbonyl at 1724 cm⁻¹ (phenolic acid esters), aromatic C=C stretching at 1598 and 1456 cm⁻¹ (flavonoids), and C-O stretching patterns indicating diverse phenolic structures. The spectral profile suggests the presence of compounds that are putatively associated with antidiabetic, antimicrobial, and anti-inflammatory activities, as documented in traditional medicine. Prominent phenolic signatures are consistent with significant antioxidant potential, while ester functionalities may point to bioactive fatty acid derivatives with antimicrobial properties. Additionally, the aromatic region fingerprints are indicative of flavonoid aglycones, which are known for their α-glucosidase inhibitory properties and potential role in diabetes management. This FTIR-based approach represents a foundational step for rapid quality assessment of Andrographis paniculata extracts, establishing a molecular basis that can guide future research into the therapeutic claims of traditional herbal medicine.